Maternal Referral Delay Factors - Ashari, Any (Chakra Brahmanda Lentera Institute, 2021)
Background: Maternal Mortality Rate (MMR) is one indicator to see the health status of women. Maternal mortality is a very important problem for received attention because death does not only affect women, but also affects the health conditions of families and communities. This is because women are the main pillars in the family who play an important role in educating children, providing health care in the family, and helping the family economy. Maternal mortality rate is an indicator that reflects maternal health status, especially the risk of death for mothers during pregnancy and childbirth. MMR in Indonesia is still quite high, Based on the 2012 Indonesian Demographic and Health Survey (IDHS), delivery, and postpartum) of 359 per 100,000 KH. Methods: This study aims to analyze the factors of delay in maternal referral, which consist of close determinants, intermediate determinants and far determinants. in hospital. PKU Muhammadiyah Gombong period 2013-2016. Results: This research uses the method of Survey with approach Cross Sectional. The population of this study were all pregnant women who experienced a maternal death in the hospital. PKU Muhammadiyah Gombong period 2013-2016. The sample in this study was to take the whole of the total population, namely all medical records of mothers who died in the hospital. PKU Muhammadiyah Gombong period 2013-2016. Data analysis was performed univariate and multivariate with SEM. Conclusion: The results of the study indicate the factors that influence mortality mother in hospital. PKU Muhammadiyah Gombong for the 2013-2016 period, both from close determinants, intermediate determinants and distant determinants are childbirth complications, postpartum complications, age, pregnancy distance, history of maternal illness, previous birth history, first birth attendant, education, place of residence, and method of delivery.